Post-abortion and post-partum breeding efficiency in Mehsani buffaloes retaining fetal membranes - NAKHASHI, H C; SUTHAR, B N; VADODARIA, V P; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The effect of retention of fetal membranes on the occurrence of first estrus and fertile estrus was studied in different groups. The occurrence of first estrus in retained fetal membranes after parturition (RFM/AP) and retained fetal membrane after abortion (RFM/ AA) were found delayed as compare to buffaloes not retaining fetal membranes after parturition (control) • with the differences being non-significant. The occurrence offertile estrus was nonsignificant between the control (85 ± 9.18 days) and RFM/AP group (113.19 ± 15.94 days) but the RFM/AA group (145.86 ± 19.85 days) differed significantly (P< 0.05). Buffaloes ofRFM/AA group required the number of inseminations 1.6 times greater than the control group.